PENGARUH INOVASI PRODUK, KUALITAS PELAYANAN DAN SOSIAL MEDIA TERHADAP KEPUTUSAN PEMBELIAN PRODUK BAKPIA KREZMERA - Sonata, Enfrada Aurora Putri; Ernestivita, Gesty; Setya Bhirawa, Sigit Wisnu (Universitas Nusantara PGRI Kediri, 2023)
This study aims to analyze and determine people's satisfaction with work motivation, work environment, and leadership style. The approach used is a quantitative causality approach. The number of respondents in this study is 40 respondents. The method used is multiple linear regression analysis processed with the help of the SPSS version 23.0 application. The results of this study indicate a coefficient of determination of 0.741. The leadership style of the Head of Ngepung Village has a positive and significant effect on community satisfaction. This is shown from the results of the t-test of 2.613 with a significance of 0.040, and a regression coefficient of 0.158. Employee work motivation has a positive and significant effect on community satisfaction. This is shown from the t-test results of 2.489 with a significance of 0.020, and a regression coefficient of 0.238. The work environment has a positive and significant effect on people's satisfaction. This is shown from the results of the t-test of 3.675 with a significance of 0.001, and a regression coefficient of 0.373. This means that 74.1% of community satisfaction at the Ngepung Village Office, Nganjuk Regency is influenced by leadership style, work motivation and work environment. While the remaining 25.9% of community satisfaction is influenced by other variables not examined in this study.